Phytochemicals Mediate the Expression and Activity of OCTN2 as Activators of the PPARγ/RXRα Pathway - Luo, Jian; Qu, Jian; Yang, Rui; Ge, Meng-Xue; Mei, Yin; Zhou, Bo-Ting; Qu, Qiang (Frontiers in Pharmacology, 2016)
Many phytochemicals exert activities as agonists of peroxisome proliferator-activated receptor gamma (PPARγ). This study aims to investigate whether phytochemicals are agonists of the PPARγ/RXRα pathway and modulate the target gene OCTN2. In this study, a luciferase reporter gene system was used to screen novel OCTN2 activators from 39 phytochemicals. Kaempferol, curcumin and puerarin were found to show the significant PPRE-mediated luciferase activities (>150%) at 20 μM and showed a dose-dependent manner. Phytochemicals also elevated the mRNA and protein expression of OCTN2 in a dose-dependent fashion in colorectal cancer SW480 cells. These induction effects were gradually inhibited by PPARγ antagonist GW9662 in the luciferase reporter gene system and in SW480 cells. Moreover, the results of cell viability assay imply that three phytochemicals probably induce OCTN2 expression leading to the enhanced uptake of its substrate, oxaliplatin, thereby making cells more sensitive to oxaliplatin. The molecular docking study showed the possible binding sites of phytochemicals in PPARγ protein, and all of the docked phytochemicals fitted the same active pocket in PPARγ as troglitazone. All three phytochemicals exhibited hydrogen bonds between their polar moieties and the amino acid residues. Thus, we identified three phytochemicals as PPARγ ligands, which potentiated the expression and activity of OCTN2.